Effect of atomic vibrations in XANES: polarization‐dependent damping of the fine structure at the Cu K‐edge of (creat)2CuCl4. (12th October 2016) - Šipr, Ondřej; Vackář, Jiří; Kuzmin, Alexei
Abstract : A technically simple method to include vibrations in X‐ray absorption near‐edge structure (XANES) calculations is used to demonstrate that vibrations have a significant effect on the polarized Cu K ‐edge spectrum of creatinium tetrachlorocuprate, (creat)2 CuCl4, even in the XANES region. Abstract : Polarization‐dependent damping of the fine structure in the Cu K ‐edge spectrum of creatinium tetrachlorocuprate [(creat)2 CuCl4 ] in the X‐ray absorption near‐edge structure (XANES) region is shown to be due to atomic vibrations. These vibrations can be separated into two groups, depending on whether the respective atoms belong to the same molecular block; individual molecular blocks can be treated as semi‐rigid entities while the mutual positions of these blocks are subject to large mean relative displacements. The effect of vibrations can be efficiently included in XANES calculations by using the same formula as for static systems but with a modified free‐electron propagator which accounts for fluctuations in interatomic distances.